DISCALCULIA: UM OLHAR PARA O ENSINO DOS NÚMEROS NATURAIS E DAS OPERAÇÕES FUNDAMENTAIS DA MATEMÁTICA - Trevisan, Marlon Cantarelli (2019)
Mathematics teachers co-exist daily with students who find it difficult to learn the contents and often question whether they relate to difficulties in teaching or learning. Aspects such as the complexity of area concepts are identified as potential for such barriers. However, nowadays, it is known that distinct problems diagnosed for learning in specific areas, such as dyscalculia, which presents as a difficulty in performing calculations and in the ordering and recognition of numbers, are known. The present work was developed in the Postgraduate Program in Teaching Science and Mathematics (PPGECIMAT) of the Franciscan University (UFN), in the research line of teacher education in science and mathematics. The purpose of this study was to construct a booklet of pedagogical guidelines on the teaching of the thematic unit "natural numbers and their fundamental operations", addressing students' learning with dyscalculia. In addition to mapping studies on the teaching of mathematics to students with learning difficulties in this area of knowledge, identify the opinion of mathematics graduates on how they are prepared to act in teaching students with dyscalculia, identify the concepts, characteristics and limitations on learning by discalcultural students, discuss the relevance of addressing the issue of learning difficulties in the training of teachers who teach mathematics and identify the opinion of mathematics teachers about their experiences and difficulties to act in teaching students with learning disorders . In this way, this research is classified as qualitative, bibliographical / documentary and exploratory / descriptive character. For the analysis of data, we chose to perform the content analysis procedure. After the construction of the booklet, a training workshop was held with graduates of the UFN pedagogy course to present and discuss the contents of the booklet. As a way of disseminating the booklet, it will be made available online, on the PPGECIMAT website, and sent to schools and teacher training courses in order to reach as many interested parties as possible. With the accomplishment of this work, it is observed the lack of material that addresses the difficulties of learning, especially the dyscalculia, aimed at assisting the teacher. Likewise, it is observed that future teachers are not being prepared to work with these students, but they are willing to discuss this matter in the training courses. Therefore, there must be a change in the curricula of the degrees to cover the learning difficulties, in the same way, it is necessary that the teachers seek to inform themselves and to form on the subject, so that the same they qualify themselves to help their students who present some diagnosis.